2x(x-5)=3

Simple and best practice solution for 2x(x-5)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x-5)=3 equation:


Simplifying
2x(x + -5) = 3

Reorder the terms:
2x(-5 + x) = 3
(-5 * 2x + x * 2x) = 3
(-10x + 2x2) = 3

Solving
-10x + 2x2 = 3

Solving for variable 'x'.

Reorder the terms:
-3 + -10x + 2x2 = 3 + -3

Combine like terms: 3 + -3 = 0
-3 + -10x + 2x2 = 0

Begin completing the square.  Divide all terms by
2 the coefficient of the squared term: 

Divide each side by '2'.
-1.5 + -5x + x2 = 0

Move the constant term to the right:

Add '1.5' to each side of the equation.
-1.5 + -5x + 1.5 + x2 = 0 + 1.5

Reorder the terms:
-1.5 + 1.5 + -5x + x2 = 0 + 1.5

Combine like terms: -1.5 + 1.5 = 0.0
0.0 + -5x + x2 = 0 + 1.5
-5x + x2 = 0 + 1.5

Combine like terms: 0 + 1.5 = 1.5
-5x + x2 = 1.5

The x term is -5x.  Take half its coefficient (-2.5).
Square it (6.25) and add it to both sides.

Add '6.25' to each side of the equation.
-5x + 6.25 + x2 = 1.5 + 6.25

Reorder the terms:
6.25 + -5x + x2 = 1.5 + 6.25

Combine like terms: 1.5 + 6.25 = 7.75
6.25 + -5x + x2 = 7.75

Factor a perfect square on the left side:
(x + -2.5)(x + -2.5) = 7.75

Calculate the square root of the right side: 2.783882181

Break this problem into two subproblems by setting 
(x + -2.5) equal to 2.783882181 and -2.783882181.

Subproblem 1

x + -2.5 = 2.783882181 Simplifying x + -2.5 = 2.783882181 Reorder the terms: -2.5 + x = 2.783882181 Solving -2.5 + x = 2.783882181 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = 2.783882181 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = 2.783882181 + 2.5 x = 2.783882181 + 2.5 Combine like terms: 2.783882181 + 2.5 = 5.283882181 x = 5.283882181 Simplifying x = 5.283882181

Subproblem 2

x + -2.5 = -2.783882181 Simplifying x + -2.5 = -2.783882181 Reorder the terms: -2.5 + x = -2.783882181 Solving -2.5 + x = -2.783882181 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = -2.783882181 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = -2.783882181 + 2.5 x = -2.783882181 + 2.5 Combine like terms: -2.783882181 + 2.5 = -0.283882181 x = -0.283882181 Simplifying x = -0.283882181

Solution

The solution to the problem is based on the solutions from the subproblems. x = {5.283882181, -0.283882181}

See similar equations:

| 3t-24=57 | | 8x+9=-143 | | 3v+17=35 | | 4v+14=32 | | 12+4x-8=48 | | ad= | | y=x^3-27x+4 | | 6(4-8a)+7=-17 | | -3x^2+8x-2=0 | | (7)(4+2x)=56 | | 64m^8-49n^6=0 | | -(9x-8)= | | -6x-5x=-11 | | -8=3x+4 | | 12x+6y=60 | | -15x^3+40x^2+35x=0 | | -35=n-17 | | -6=3(3+k) | | 6-(-10)= | | 5-4x-5=-8 | | -77=8x+3 | | -126=-18r | | -11=x-6 | | w^2-6w-8=0 | | 7a+8=57 | | 4(3-x)-8=5-(3x-2) | | 4u^2-25u+25=0 | | 53+(-18)= | | 52+-50= | | 5.4c+6=0.6(9c+10) | | 3t+7=13 | | 5x-6x-5=72 |

Equations solver categories